Energy use, economic growth, energy subsidies, CO2 emissions towards population growth - Taufiq C. Dawood, Al Yuda Suci Pratama, Aliasuddin, (Opción, 2020)
This study examines the influence of energy consumption, economic growth, energy subsidies, population growth on CO2 emissions by using methods Generalized Method of Moment (GMM). GMM testing found that oil prices and significant variables have a negative effect on CO2 emissions. Meanwhile, economic growth and population growth and energy consumption have a positive effect on carbon dioxide emissions in Indonesia. In conclusion, the oil price variable is a negative effect and significant to carbon dioxide while other variables such are economic growth, population and energy consumption showed the positive result of the increase of carbon dioxide in Indonesia.